Longer combination vehicles and road safety - Grīslis, Aivis (Transport, 2010)
The aim of this paper is to explore the relationship between the features of Longer Combination Vehicles (LCVs) and road safety issues. LCVs are road vehicles that exceed dimensions of a typical or standard heavy truck‐trailer or tractor‐semitrailer combination vehicles in length or length and weight. The systematization of LCVs is done. Several areas, which are likely to benefit through LCVs, are listed and described. The analysis of literature review is made in the areas where additional problems may be encountered using LCVs. Several engineering factors such as resistance to rollover, swept‐path parameters, vehicle capabilities of accelerating and maintaining speed as well as braking performance are analyzed. Several research projects on traffic accident analysis have been looked through to compare their conclusions about traffic safety of LCVs. The analysis of discussions related to LCVs traffic safety issues is provided. Some transportation experts and community groups have conflicting views about road safety issues of LCVs. The opinions and related arguments of both parties are discussed in this paper. Several technical improvements in designing LCVs and the importance of driver training programs are described. First published online: 10 Feb 2011